Anti-HIV activity of southern African plants: Current developments, phytochemistry and future research. (10th January 2018) - Prinsloo, Gerhard; Marokane, Cynthia K.; Street, Renée A.
Abstract: Ethnopharmacological relevance: The African continent is home to a large number of higher plant species used over centuries for many applications, which include treating and managing diseases such as HIV. Due to the overwhelming prevalence and incidence rates of HIV, especially in sub-Saharan Africa, it is necessary to develop new and affordable treatments. Aim of the study: The article provides an extensive overview of the status on investigation of plants from the southern African region with ethnobotanical use for treating HIV or HIV-related symptoms, or the management of HIV. The review also provide an account of the in vitro assays, anti-viral activity and phytochemistry of these plants. Materials and methods: Peer-reviewed articles investigating plants with ethnobotanical information for the treatment or management of HIV or HIV-related symptoms from the southern African region were acquired from Science Direct, PubMed central and Google Scholar. The selection criteria was that (1) plants should have a record of traditional/popular use for infectious or viral diseases, HIV treatment or symptoms similar to HIV infection, (2) if not traditionally/popularly used, plants should be closely related to plants with popular use and HIV activity identified by means of in vitro assays, (3) plants should have been identified scientifically, (4) should be native to southern African region and (5) anti-HIV activity should be within acceptable ranges. Results: Many plants in Africa and specifically the southern African region have been used for the treatment of HIV or HIV related symptoms and have been investigated suing various in vitro techniques. In vitro assays using HIV enzymes such as reverse transcriptase (RT), integrase (IN) and protease (PR), proteins or cell-based assays have been employed to validate the use of these plants with occasional indication of the selectivity index (SI) or therapeutic index (TI), with only one study, that progressed to in vivo testing. The compounds identified from plants from southern Africa is similar to compounds identified from other regions of the world, and the compounds have been divided into three groups namely (1) flavonoids and flavonoid glycosides, (2) terpenoids and terpenoid glycosides and (3) phenolic acids and their conjugated forms. Conclusions: An investigation of the plants from southern Africa with ethnobotanical use for the treatment of HIV, management of HIV or HIV-related symptoms, therefore provide a very good analysis of the major assays employed and the anti-viral compounds and compound groups identified. The similarity in identified anti-viral compounds worldwide should support the progression from in vitro studies to in vivo testing in development of affordable and effective anti-HIV agents for countries with high infection and mortality rates due to HIV/AIDS. Graphical abstract: